Entanglements in marginal solutions: a means of tuning pre-aggregation of conjugated polymers with positive implications for charge transport1. Issue 28 (28th July 2015) - Hu, Hanlin; Zhao, Kui; Fernandes, Nikhil; Boufflet, Pierre; Bannock, James H.; Yu, Liyang; de Mello, John C.; Stingelin, Natalie; Heeney, Martin; Giannelis, Emmanuel P.; Amassian, Aram
<x xml:space="preserve">Abstract</x> Marginal solutions of conjugated polymers are increasingly common in organic electronic applications. We demonstrate how to controllably induce aggregation in such solutions with the aim of altering microstructure and transport properties.